INFLUENCE COMPENSATION, WORKING ENVIRONMENT AND LEADERSHIP ON THE PERFORMANCE OF MARINE EMPLOYEES PT. JEMLA FERRY KETAPANG-GILIMANUK BRANCH - Geri Damayanto; Muhammad Firdaus; Agustin, HP (SEAN Institute, 2023)
In general, the purpose of this research is to test and analyze the effect significant from Compensation, Work Environment and Leadership on the Performance of sea employees, especially on ships owned by PT. JEMLA Ferry Ketapang-Gilimanuk branch, namely KMP. Gilimanuk and KMP. Gilimanuk II. This study uses data collection and data analysis that is statistical/quantitative in nature with the aim of testing the established hypothesis. The number of respondents was 49 people sea employees both officers and crew as a whole on both ships, with saturated sample techniques. The research results obtained show that the conditions on board the ship comprised Compensation, Work Environment and Leadership simultaneously have a significant influence on sea employee performance. Supported by empirical data showing that partially the work environment has a significant influence on the performance of marine employees. Meanwhile, compensation and leadership from the results of the study showed results that were not significant to the performance of marine employees.